Belajar Dalam Perspektif Psikologi dan Agama - Dewi, Chandra (STAI Serdang Lubuk Pakam, 2019)
Learning is a process of activity and is a very fundamental element in the implementation of each type and level of education. Simply stated, learning is the process of finding one's identity for character building so that individuals are able to position themselves and be accepted in the social environment. Learning, of course, is inseparable from the utilization of the work of the brain related to memory or reception, storage and application of learning outcomes. Understanding of learning every child must be different, influenced by various aspects. Of the various aspects that affect the learning process, the important thing to remember parents and teachers is how to create a learning atmosphere that does not burden the child or even learning to be fun for all children. With this background, the author takes the title